A sodium niobate-based antiferroelectric ceramic material and its preparation method and application

By doping Bi0.2Sr0.7SnO3 and oxygen annealing treatment in sodium niobate ceramics, the conversion problem of traditional sodium niobate ceramics under large electric fields is solved, and the stability and energy storage efficiency of its antiferroelectric phase are improved. It is suitable for High-performance dielectric capacitors.

CN116535210BActive Publication Date: 2025-01-03SOUTH CHINA UNIV OF TECH
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202310388194.6
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-04-12
Publication Date
2025-01-03
Estimated Expiration
2043-04-12

AI Technical Summary

Technical Problem

Traditional sodium niobate ceramics are easily irreversibly converted into ferroelectric phase under large external electric fields, resulting in low energy storage density and energy storage efficiency. The existing technology is difficult to stabilize the antiferroelectric phase, which limits its application in dielectric capacitors.

Method used

By doping Bi0.2Sr0.7SnO3, the polarization rate of tolerance factor and B-position ions is reduced, combined with the oxygen atmosphere annealing process, the antiferroelectric phase stability and breakdown strength of the ceramic are improved, and polar nano micro-domains are formed, which is enhanced. Energy storage efficiency.

Benefits of technology

It realizes high energy storage efficiency and low dielectric loss, moderate dielectric constant and low dielectric loss of sodium niobate-based antiferroelectric ceramics, and is suitable for high-performance dielectric capacitors.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN116535210B_ABST
    Figure CN116535210B_ABST
Patent Text Reader

Abstract

The invention discloses a sodium niobate-based antiferroelectric ceramic material and a preparation method and application thereof; the molecular formula of the ceramic material is (1-x)NaNbO3-xBi 0.2 Sr 0.7 SnO3, wherein 0.10≤x≤0.20. The present invention prepares a ceramic material by uniformly mixing a sodium source, a niobium source, a bismuth source, a strontium source and a tin source according to the stoichiometric ratio of Na, Nb, Bi, Sr and Sn in the molecular formula, and calcining the resultant ceramic powder; the ceramic powder is formed and debonded, and then sintered and annealed to obtain the ceramic material. The present invention provides a novel doping strategy and preparation technology, which has a simple process and is easy to operate. The invention is suitable for the preparation and application of ceramic capacitors and dielectric capacitors in high-power pulse systems, and provides a new idea for improving the energy storage characteristics of sodium niobate-based antiferroelectric ceramic materials.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of functional ceramics, and in particular to a sodium niobate-based antiferroelectric ceramic material and a preparation method and application thereof. Background Art

[0002] In power electronic systems, such as pulsed power weapons, electric vehicles, and aircraft, dielectric energy storage capacitors play an important role. However, the energy storage density of dielectric capacitors is poor, which greatly limits their commercial applications. In addition, another aspect that needs to be considered is the environmentally friendly characteristics. Therefore, in order to meet the growing demand for dielectric capacitors, it is imperative to study new high-performance and environmentally friendly dielectric materials.

[0003] Traditional linear dielectric materials have extremely high efficiency, but their small dielectric constant limits the growth of energy storage density. Nonlinear dielectric materials, such as ferroelectric, antiferroelectric and relaxor ferroelectric ceramic materials, are promising in energy storage applications. Among them, antiferroelectric ceramic materials are considered to be the main candidate materials for energy storage capacitors due to their high saturation polarization and low remanent polarization.

[0004] Unmodified sodium niobate ceramics are a typical lead-free antiferroelectric ceramic with the advantages of low cost, light weight and non-toxicity. However, when a large external electric field is applied to sodium niobate ceramics, its antiferroelectric phase tends to irreversibly transform into a ferroelectric phase, resulting in low energy storage density and energy storage efficiency of unmodified sodium niobate ceramics, with an energy storage density of about 0.4 J / cm 3 , the energy storage efficiency is about 10% (Realizing ultrahigh recoverable energy density and superior charge–discharge performance in NaNbO3-based lead-free ceramics via a localrandom field strategy, DOI: 10.1039 / c9tc06711).

[0005] In order to solve this problem, researchers have made a lot of assumptions on how to stabilize the antiferroelectric phase. In summary, the following two factors affect the stability of the antiferroelectric phase in the perovskite system: (1) reducing the tolerance factor. A smaller tolerance factor is more conducive to the generation of antibulk distortion, so the tolerance factor is an important factor affecting the stability of the antiferroelectric phase; (2) reducing the polarizability of the B-site ions is another important strategy to stabilize the antiferroelectric phase. Low ion polarizability helps to strengthen ionic bonds, especially to produce short-range ordered polar clusters, thereby reducing P r , improve energy storage efficiency. Summary of the invention

[0006] In view of the shortcomings of the prior art, the present invention aims to provide a sodium niobate-based antiferroelectric ceramic material for energy storage and a preparation method and application thereof. The present invention adopts a new doping strategy and preparation process to improve the energy storage properties of the sodium niobate-based ceramic material. The molecular formula of the doped compound is Bi 0.2 Sr 0.7 SnO3, through doping, can reduce the tolerance factor of the system. At the same time, the ion polarization rate of the Sn source is low, and the Bi source can hybridize with the oxygen element to improve the A-site polarization. The annealing process in an oxygen atmosphere can effectively improve the breakdown strength of the ceramic, providing a new idea for the development of dielectric capacitors with high energy storage characteristics.

[0007] The purpose of the present invention is achieved through the following technical solutions:

[0008] According to one aspect of the present invention, a sodium niobate-based antiferroelectric ceramic material is provided, wherein the molecular formula of the ceramic material is (1-x)NaNbO3-xBi 0.2 Sr 0.7 SnO3, wherein 0.10≤x≤0.20.

[0009] The sodium niobate-based antiferroelectric ceramic material of the present invention is used for energy storage electrical components, including lead-free sodium niobate-based antiferroelectric ceramic components, ceramic components for dielectric energy storage capacitors, and the like.

[0010] According to another aspect of the present invention, the present invention provides a method for preparing the above-mentioned sodium niobate-based antiferroelectric ceramic material, comprising the following steps:

[0011] (1) mixing a sodium source, a niobium source, a bismuth source, a strontium source, and a tin source uniformly according to the stoichiometric ratio of Na, Nb, Bi, Sr, and Sn in the molecular formula, and calcining to synthesize a ceramic powder;

[0012] (2) After the ceramic powder is formed and debinded, it is sintered and annealed to obtain the ceramic material.

[0013] Preferably, the sodium source in step (1) is Na2CO3; and the niobium source is Nb2O5.

[0014] Preferably, in step (1), the bismuth source is Bi2O3; the strontium source is SrO; and the tin source is SnO2.

[0015] Preferably, the calcination temperature in step (1) can be 900-1000° C., and the holding time can be 1-24 hours.

[0016] Preferably, the debinding temperature in step (2) is 600-800° C., and the insulation time is 1-24 hours.

[0017] Preferably, the sintering temperature in step (2) is 1320-1370° C., and the holding time is 1-24 hours.

[0018] Preferably, the sintering in step (2) is carried out in an air atmosphere.

[0019] Preferably, the annealing in step (2) is performed in an oxygen atmosphere;

[0020] Preferably, the annealing temperature in step (2) is 1000-1200° C., and the holding time is 1-24 hours.

[0021] The present invention also provides a ceramic component which is made of the above ceramic material or contains the above sodium niobate-based antiferroelectric ceramic material.

[0022] Preferably, the ceramic material is processed into a desired size and then silvered and silver-sintered.

[0023] Compared with the prior art, the present invention has the following beneficial effects:

[0024] The technical solution of the present invention successfully prepares lead-free sodium niobate-based antiferroelectric ceramics by component regulation and solid phase reaction method, and further improves the energy storage characteristics of the ceramics by annealing process. The lead-free sodium niobate-based antiferroelectric ceramics are measured to have the characteristics of pure perovskite phase structure, moderate dielectric constant and low dielectric loss, high energy storage efficiency, etc. BRIEF DESCRIPTION OF THE DRAWINGS

[0025] Figure 1 This is Example 1 of the present invention (0.90NaNbO3-0.10Bi 0.2 Sr 0.7 SnO3), Example 2 (0.85NaNbO3-0.15Bi 0.2 Sr 0.7 SnO3), Example 3 (0.80NaNbO3-0.20Bi 0.2 Sr 0.7 SnO3), Comparative Example 1 (0.94NaNbO3-0.06Bi 0.2 Sr 0.7 X-ray diffraction pattern of SnO3);

[0026] Figure 2 is a curve showing the change of dielectric constant and dielectric loss with temperature in Example 1 of the present invention;

[0027] Figure 3 is a curve showing the change of dielectric constant and dielectric loss with temperature in Example 2 of the present invention;

[0028] Figure 4 is a curve showing the change of dielectric constant and dielectric loss with temperature in Example 3 of the present invention;

[0029] Figure 5 1 is a curve showing the change of dielectric constant and dielectric loss with temperature in comparative example 1 of the present invention. DETAILED DESCRIPTION

[0030] In order to make the purpose and advantages of the present invention more clearly understood, the embodiments of the present invention will now be described more fully with reference to the examples, which will help those skilled in the art to further understand the present invention, however, the embodiments of the present invention can be implemented in various forms and should not be understood as being limited to the embodiments described herein. On the contrary, these embodiments are provided so that the present invention will be comprehensive and complete, and the concept of the exemplary embodiments will be fully conveyed to those skilled in the art.

[0031] The embodiment of the present invention provides a sodium niobate-based antiferroelectric ceramic material and a preparation method thereof;

[0032] Its chemical composition is (1-x)NaNbO3-xBi 0.2 Sr 0.7 SnO3, wherein 0.10≤x≤0.20, x is a molar percentage.

[0033] The present invention has been verified through theoretical research and multiple experiments. Aiming at the metastable ferroelectricity of sodium niobate-based ceramics, the stability of the antiferroelectric phase is enhanced by reducing the system tolerance factor and the polarizability of the B-site ions. At the same time, the A-site polarization is improved by orbital hybridization, and the breakdown strength is improved by annealing in an oxygen atmosphere. In addition, due to Bi 3+ , Sr 2+ Sn 4+ with Na + and Nb 5+ The valence states of the atoms are different. This unequal doping will destroy the long-range order of the structure, form polar nano-regions, and lead to relaxation behavior, which is beneficial to improving the energy storage efficiency of ceramics.

[0034] Preferably, within the composition range of 0.10≤x≤0.20, a dielectric temperature spectrum with a moderate dielectric constant and low dielectric loss can be observed.

[0035] The preparation method of the sodium niobate-based antiferroelectric ceramic material disclosed in the present invention can be prepared by a solid phase reaction process and annealed, for example, it can include the steps of batching, mixing, synthesis, crushing, fine grinding, molding, debinding, sintering, annealing, etc. The preparation method of the sodium niobate-based antiferroelectric ceramic material is exemplified below.

[0036] Step 1, preparing ceramic powder by solid phase method, specifically, sodium source, niobium source, bismuth source, strontium source and tin source according to their respective elements in (1-x)NaNbO3-xBi 0.2 Sr 0.7The stoichiometric ratio in SnO3 is uniformly mixed to synthesize the required ceramic powder.

[0037] Sodium carbonate (Na2CO3) can be used as a sodium source, niobium oxide (Nb2O5) can be used as a niobium source, bismuth oxide (Bi2O3) can be used as a bismuth source, (SrO) can be used as a strontium source, and tin oxide (SnO2) can be used as a tin source.

[0038] The raw materials can be evenly mixed by ball milling. The mass ratio of raw materials: balls: alcohol is 1: (2-4): (0.8-1.5). The ball milling medium can be zirconium balls, agate balls, etc. The ball milling (mixing) time can be 10-48 hours. It can be dried after ball milling and sieved (for example, 20-80 mesh sieve). The synthesis (calcination) temperature of step 1 can be 900-1050°C. Preferably, the temperature is increased to the synthesis temperature at a heating rate not higher than 2°C / min. Thereby, the reaction can be fully occurred. The insulation time at the synthesis temperature can be selected from 1 to 24 hours, preferably 2 to 5 hours.

[0039] After calcination, the powder can be cooled to room temperature with the furnace. During calcination, the powder can be placed in a closed container (such as a closed alumina crucible) for synthesis, thereby reducing the volatilization of Na and Bi components. After synthesis, the powder can be crushed and ground, thereby improving the efficiency of the subsequent ball milling process and saving preparation time.

[0040] Step 2, pressing the obtained sodium niobate-based ceramic powder into a shape and removing binder to obtain a ceramic green body. The sodium niobate-based ceramic powder can be finely ground before forming. The fine grinding method can be a wet ball milling method. The mass ratio of ceramic powder: ball: alcohol can be 1: (2-4): (0.8-1.5). The ball milling medium can be a zirconium ball, agate ball, etc. The ball milling time can be 10-48 hours. It can be dried after fine grinding.

[0041] Add a binder for granulation. The binder used in granulation can be polyvinyl alcohol (PVA) or the like, the concentration of the binder is 5-10%, and the amount added can be 5-7% of the weight of the ceramic powder. After granulation, it can be aged for a period of time, and then pressed into shape after aging. The aging time can be 24-48 hours. The molding process can include: dry-pressing the prepared powder to obtain a green body of the desired size. The pressing pressure can be 100-300 MPa. After molding, the temperature is increased to discharge the plastic, and the discharge conditions can be: heating to 600-800°C at a heating rate not higher than 2°C / min, keeping warm for 1-24 hours, preferably 2-6 hours, and cooling to room temperature with the furnace.

[0042] Next, the obtained ceramic green body is sintered. The sintering temperature can be 1320-1370°C, and the holding time can be 1-24 hours, preferably 2-6 hours. In a preferred embodiment, the temperature is raised to 1320-1370°C at a heating rate of not more than 2°C / minute, so that the ceramic can be easily formed into porcelain without causing component segregation. The sintering can be carried out in a high-temperature furnace, and after sintering, the furnace can be cooled to room temperature.

[0043] Finally, the sintered ceramic is annealed in an oxygen atmosphere at a temperature of 1000-1200°C for 1-24 hours, preferably 2-6 hours. In a preferred embodiment, the temperature is raised to 1000-1200°C at a heating rate of no more than 2°C / min, and the ceramic is cooled to room temperature in the furnace after annealing.

[0044] Also disclosed herein is a sodium niobate-based antiferroelectric ceramic element, which is made using the sodium niobate-based antiferroelectric ceramic material. In one example, the ceramic material is processed into a desired size, cleaned (e.g., ultrasonically cleaned), dried, silvered, and silver-sintered to obtain a sodium niobate-based antiferroelectric ceramic element. The silver-sintering condition can be to keep the temperature at 500 to 800° C. for 10 to 30 minutes, and after silver-sintering, the furnace can be cooled to room temperature.

[0045] The lead-free sodium niobate-based antiferroelectric ceramic material of the embodiment of the present invention has the characteristics of high energy storage efficiency and low dielectric loss. For example, in one example, for the component x=0.10, its energy storage efficiency can reach 85.3%.

[0046] The present invention is described below with specific embodiments:

[0047] Example 1

[0048] A sodium niobate-based antiferroelectric ceramic material for energy storage, with the molecular formula (1-x)NaNbO3-xBi 0.2 Sr 0.7 SnO3, wherein x=0.10.

[0049] The present invention is prepared by a solid phase sintering method, specifically according to the following steps:

[0050] (1) According to the molecular formula (1-x) NaNbO3-xBi of the present invention 0.2 Sr 0.7 SnO3, wherein x=0.10 is used for ingredient calculation, and the required raw materials are: sodium carbonate with a purity of 99.99%, niobium oxide with a purity of 99.99%, bismuth oxide with a purity of 99.99%, strontium oxide with a purity of 99.99%, and tin oxide with a purity of 99.99%; an electronic balance is used for weighing, and the weighing accuracy is 0.0001g.

[0051] (2) The weighed raw materials are mixed and placed in a nylon jar, anhydrous ethanol is added to the jar, and zirconium oxide balls of different sizes are used as ball milling media. The nylon jar is placed on a planetary ball mill and mixed for 10 hours, wherein the mass ratio of the raw materials, zirconium oxide balls, and anhydrous ethanol is 1:2:2 respectively; the raw materials are then poured out and dried in a baking oven, and then calcined at 950°C, kept warm for 4 hours, and then crushed through a 60-mesh sieve to obtain a ceramic powder.

[0052] (3) The obtained powder is put into a nylon jar again, and anhydrous ethanol is added to the jar at a level not higher than 2 / 3 of the height of the jar. The nylon jar is placed on a planetary ball mill with zirconium oxide balls as the medium and mixed for 10 hours. The nylon jar is then poured out and dried in an oven, and then sieved with a 60-mesh nylon sieve to obtain finely ground powder.

[0053] (4) Add a 5 wt% polyvinyl alcohol aqueous solution to the ground ceramic powder, the amount of polyvinyl alcohol aqueous solution added is 6% of the mass of the ceramic powder, then granulate evenly, pass through a 100-mesh sieve, and press-form to obtain small cylinders with a diameter of 15 mm, and perform debinding (600°C, insulation for 3 h).

[0054] (5) The green body obtained after debinding was sintered in air atmosphere at a sintering temperature of 1370°C for 2 hours at a heating and cooling rate of 2°C / min. The sample was taken out after naturally cooling to room temperature.

[0055] (6) The sintered ceramic was annealed in an oxygen atmosphere at a temperature of 1200°C, a holding time of 2 hours, a heating rate of 2°C / min, and the sample was taken out after naturally cooling to room temperature.

[0056] (7) The sintered ceramic sample is processed, cleaned, dried, and electroded to obtain a ceramic component.

[0057] X-ray diffraction test was carried out on the prepared sodium niobate-based ferroelectric ceramic material. Figure 1 The X-ray diffraction pattern of Example 1 is shown. It can be seen that the obtained example ceramic is a pure phase.

[0058] The prepared ceramic element was subjected to hysteresis loop test at room temperature and 10 Hz. The main performance parameters obtained according to the test results are shown in Table 1.

[0059] The dielectric properties were tested using a dielectric impedance spectrometer. The results are attached. Figure 2 .

[0060] Example 2

[0061] A sodium niobate-based antiferroelectric ceramic material for energy storage, with the molecular formula (1-x)NaNbO3-xBi 0.2 Sr 0.7 SnO3, wherein x=0.15.

[0062] The preparation method of Example 1 was repeated according to the above chemical formula; except that the value of x in step (1) was different, the other steps were the same as those of Example 1.

[0063] According to the molecular formula (1-x) NaNbO3-xBi of the present invention 0.2 Sr 0.7 SnO3, where x=0.15 for batching calculation.

[0064] The prepared sodium niobate-based ferroelectric ceramic material was subjected to X-ray diffraction test. Figure 1 The X-ray diffraction pattern of Example 2 is shown. It can be seen that the obtained ceramic of Example has a typical perovskite structure, and no impurity phase is detected.

[0065] The ceramic element prepared in Example 2 was subjected to a hysteresis loop test at room temperature and 10 Hz. The main performance parameters obtained based on the test results are shown in Table 1.

[0066] The dielectric properties were tested using a dielectric impedance spectrometer. The results are attached. Figure 3 .

[0067] Example 3

[0068] A sodium niobate-based antiferroelectric ceramic material with the molecular formula (1-x)NaNbO3-xBi 0.2 Sr 0.7 SnO3, wherein x=0.20.

[0069] The preparation method of Example 1 was repeated according to the above chemical formula; except that the value of x in step (1) was different, the other steps were the same as those of Example 1.

[0070] According to the molecular formula (1-x) NaNbO3-xBi of the present invention 0.2 Sr 0.7 SnO3, where x=0.20 for batching calculation.

[0071] X-ray diffraction test was carried out on the prepared sodium niobate-based antiferroelectric ceramic material. Figure 1 The X-ray diffraction pattern of Example 3 is shown. It can be seen that the obtained ceramic has no impurity phase.

[0072] The ceramic element prepared in Example 1 was subjected to a hysteresis loop test at room temperature and 10 Hz. The main performance parameters obtained according to the test results are shown in Table 1.

[0073] The dielectric properties were tested using a dielectric impedance spectrometer. The results are attached. Figure 4 .

[0074] Comparative Example 1

[0075] A sodium niobate-based antiferroelectric ceramic material with no relaxation properties, the molecular formula is (1-x)NaNbO3-xBi 0.2 Sr 0.7 SnO3, wherein x=0.06.

[0076] The preparation method of Example 1 was repeated according to the above chemical formula; except that the value of x in step (1) was different, the other steps were the same as those of Example 1.

[0077] According to the molecular formula (1-x) NaNbO3-xBi of the present invention 0.2 Sr 0.7 SnO3, where x=0.06 for batching calculation.

[0078] The prepared sodium niobate-based antiferroelectric ceramic material was subjected to X-ray diffraction test. Figure 1 The X-ray diffraction pattern of Comparative Example 1 is shown. It can be seen that the obtained ceramic has no impurity phase.

[0079] The ceramic element prepared in Comparative Example 1 was subjected to a hysteresis loop test at room temperature and 10 Hz. The main performance parameters obtained according to the test results are shown in Table 1.

[0080] The dielectric properties were tested using a dielectric impedance spectrometer. The results are attached. Figure 5 .

[0081] Result analysis:

[0082] from Figure 1 It can be seen that Bi 0.2 Sr 0.7 SnO3-doped NaNbO3 ceramics in Examples 1, 2, 3 and Comparative Example 1 all have typical perovskite structures, and no obvious second phase is observed, indicating that Bi 0.2 Sr 0.7 SnO3 can diffuse well into the NaNbO3 lattice. In order to further study the phase structure of the sample, the (110) and (200) peaks near 32.5° and 46.5° were locally amplified. 0.2 Sr 0.7 ) 2+ Average radius Less than At site B, Sn 4+ Radius Greater than Nb 5+ Radius However, the (110) and (200) peaks move to lower angles with the addition of BSS. According to the Bragg diffraction equation, this is due to the expansion of the lattice volume. In addition, split (110) and (200) diffraction peaks were observed in the 0.94NN-0.06BSS component. With the increase of BSS doping, the split diffraction peaks merged into a single peak, indicating that the sample underwent a phase transition from the orthorhombic phase to the pseudo-cubic phase.

[0083] Table 1 describes the relevant energy storage parameters of Example 1, Example 2, Example 3 and Comparative Example 1. The effective energy storage density of Examples 1, 2 and 3 is 2.31 J / cm 3 , 2.09J / cm 3 and 1.51 J / cm 3 The energy storage efficiencies are 85.3%, 83.9% and 84.3% respectively.

[0084] The energy storage density of comparative example 1 is 1.06 J / cm 3 , the energy storage efficiency is only 61.2%, which is not ideal for dielectric capacitors.

[0085] By comparison, it is obvious that Example 1, Example 2, and Example 3 have better energy storage characteristics than Comparative Example 1, and are more suitable for application in pulse power capacitor technology.

[0086] Table 1 Related energy storage parameters of Examples 1, 2, 3 and Comparative Example 1

[0087]

[0088] Figure 2 , 3 , 4, 5 are respectively the curves of the dielectric constant variation with temperature at 10kHz for Examples 1, 2, 3 and Comparative Example 1. Figure 2 As shown in Figure 1, in Example 1, the existence of a dielectric peak can be observed near -120°C. The decrease of the Curie temperature below room temperature indicates that the sample begins to transform into a paraelectric phase at room temperature, which is consistent with the XRD analysis results. In addition, the dielectric peak is relatively flat, which proves the existence of relaxation characteristics. The existence of relaxation characteristics is conducive to the improvement of energy storage efficiency. Figure 3 , 4 As shown in Examples 2 and 3, no dielectric peak can be observed in the temperature range of -150°C to 300°C, but according to Figure 3 , 4 The trend of can infer that its dielectric peak is below -150℃. Figure 5As shown, in Comparative Example 1, a sharp dielectric peak can be observed at about 250°C, which is related to the transition from the AFE orthogonal P phase to the PE phase, indicating the existence of the antiferroelectric P phase at room temperature. In addition, in the temperature range of -150 to 200°C, the dielectric loss of Examples 1, 2, 3 and Comparative Example 1 is less than 0.05, indicating that the stability of the ceramic is very good in this temperature range.

[0089] In summary, the embodiments of the present invention are 0.2 Sr 0.7 SnO3 doping stabilizes the antiferroelectric phase of sodium niobate-based ceramics, and with the addition of Bi 0.2 Sr 0.7 The increase of SnO3 doping can form polar nano-microregions and induce relaxation behavior, which greatly improves the energy storage efficiency of sodium niobate-based ceramics. At the same time, annealing in an oxygen atmosphere can inhibit the formation of oxygen vacancies and improve the energy storage density of sodium niobate-based ceramics. This doping strategy and preparation process can be used for ceramic capacitors and dielectric capacitors in high-power pulse systems.

[0090] The above contents are further detailed descriptions of the present invention in combination with specific preferred embodiments, and it cannot be determined that the specific implementation of the present invention is limited to these descriptions. For ordinary technicians in the technical field to which the present invention belongs, several simple deductions or substitutions can be made without departing from the concept of the present invention, which should be regarded as falling within the protection scope of the present invention.

Claims

1. A sodium niobate-based antiferroelectric ceramic material, characterized in that: The molecular formula of the ceramic material is (1-x)NaNbO3-xBi 0.2 Sr 0.7 SnO3, where 0.10≤x≤0.15; The preparation method of the sodium niobate-based antiferroelectric ceramic material comprises the following steps: (1) mixing a sodium source, a niobium source, a bismuth source, a strontium source, and a tin source uniformly according to the stoichiometric ratio of Na, Nb, Bi, Sr, and Sn in the molecular formula, and calcining to synthesize a ceramic powder; The calcination temperature is 900-1000°C and the holding time is 2-5 hours; (2) forming and debinding the ceramic powder, and then sintering and annealing the ceramic powder to obtain the ceramic material; The sintering temperature is 1320-1370°C, and the holding time is 2-6 hours; the sintering is carried out in an air atmosphere; The annealing is carried out in an oxygen atmosphere; the annealing temperature is 1000-1200° C., and the heat preservation time is 2-6 hours.

2. The method for preparing the sodium niobate-based antiferroelectric ceramic material according to claim 1, characterized in that: The following steps are involved: (1) mixing a sodium source, a niobium source, a bismuth source, a strontium source, and a tin source uniformly according to the stoichiometric ratio of Na, Nb, Bi, Sr, and Sn in the molecular formula, and calcining to synthesize a ceramic powder; The calcination temperature is 900-1000°C and the holding time is 2-5 hours; (2) forming and debinding the ceramic powder, and then sintering and annealing the ceramic powder to obtain the ceramic material; The sintering temperature is 1320-1370°C, and the holding time is 2-6 hours; the sintering is carried out in an air atmosphere; The annealing is carried out in an oxygen atmosphere; the annealing temperature is 1000-1200° C., and the heat preservation time is 2-6 hours.

3. The preparation method according to claim 2, characterized in that: In step (1), the sodium source is Na2CO3; the niobium source is Nb2O5; the bismuth source is Bi2O3; the strontium source is SrO; and the tin source is SnO2.

4. The preparation method according to claim 2, characterized in that: The debinding temperature in step (2) is 600-800° C., and the insulation time is 1-24 hours.

5. A ceramic component, characterized in that: The sodium niobate-based antiferroelectric ceramic material according to claim 1 is made by using the sodium niobate-based antiferroelectric ceramic material according to claim 1 or contains the sodium niobate-based antiferroelectric ceramic material according to claim 1.

6. The ceramic component according to claim 5, characterized in that The ceramic element is made by processing the sodium niobate-based antiferroelectric ceramic material into a desired size and then silvering and sintering the silver.

Citation Information

Patent Citations

  • Potassium sodium niobate-based ferroelectric ceramic material with high energy storage efficiency and density and preparation method thereof

    CN113213929A

  • Preparation method of lead-free ferroelectric film with high energy storage density

    CN115386837A